(untitled) (Journal of Medical & Health Sciences Review, 2025)
Annual appraisal is a crucial tool for evaluating nurses’ performance and identifying areas for improvement. However, its impact on nurses’ competencies in tertiary care settings is not well understood. To investigate the impact of annual performance appraisal on nurses’ competencies in a tertiary care hospital. A cross-sectional study was conducted among 30 nurses working in a tertiary care hospital. Data was collected using a structured questionnaire and annual appraisal reports. Nurses who received regular feedback and coaching during annual appraisals reported higher levels of competency in patient care, communication, and teamwork. Annual appraisal has a positive impact on nurses’ competencies in tertiary care settings. Healthcare institutions should implement clear and standardized performance appraisal systems that are well-understood by both appraisers and appraisers. It is essential to provide continuous feedback, not just during annual appraisals, to ensure that nurses have ongoing guidance and support to improve their competencies.